Jurnal Pekerjaan Sosial Indonesia: Hardiness Perempuan Rawan Sosial Ekonomi Sebagai Single Parent Dalam Memenuhi Kebutuhan Ekonomi Keluarga di Kelurahan Cipadung Kulon Kecamatan Panyileukan Kota Bandung - Grace Miranda Ruth Nauli Nainggolan; Dede Kuswanda (Politeknik Kesejahteraan Sosial Bandung, 2023)
Hardiness is a self characteristic that can help someone to survive in a difficult situation by having a commitment, control, and challenge aspect to grow. This research is aim to obtain empirical depictions of the characteristic of the respondents, commitment of the social-economic vulnerable women as a single parent in fulfilling family economic needs, control of the social-economic vulnerable women as a single parent in fulfilling family economics needs and challenges of social economic vulnerable women as a single parent in fulfilling family economics needs. This research uses a descriptive method with a quantitative approach. The data resources of this research are primary and secondary data. Data collection techniques used are questionnaires and documentation studies. The measuring instrument used a rating scale statement with multiple choices and face validity. The result showed research about the hardiness of socially-economic vulnerable women as single parents in fulfilling family economic needs in Cipadung Kulon in a high category. However, the hardiness characteristics of socio-economically vulnerable women are needed to be more maintained it is the aim of making the hardiness in women with socio-economic vulnerability stronger and making their resilience to survive better. Therefore, the researcher proposes a program named